FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MEROKOK PADA REMAJA DI RW 06 KURARO ATAS KELURAHAN KOTA RATU ENDE - Marthina Bedho (Kelimutu Nursing Journal, 2022)
Youth is the future successor of the nation. But they were faced with a severe problem and difficult to overcome in achieving expectations. Various factors can affect teenagers, one of them is smoking. Smoking can lower one's health. If smoking since adolescence will threaten health. WHO data say smoking is the cause of almost 90% of lung cancer, 75% COPD, and 25% cause of heart attacks. Indonesian adolescents experience various diseases due to smoking, namely lung cancer 60.1%, 25% stroke and other diseases 12.5%. The highest smoker was East Nusa Tenggara with 55.6%, with the first teenage smoker at 17.7% from 34 provinces in Indonesia. Researchers observed in Ende City namely in RW 06 Kuraro Atas from 25 adolescents, who smoked 18 people. This study aimed to investigate factors affecting smoking behaviour and the impact of smoking on adolescents in RW 06 Kuraro Upper Kelurahan Kota Ratu Kecamatan Ende Utara Kabupaten Ende. Descriptive research with cross-sectional design. The number of respondents was 18 teenagers using total sampling. The study reported that from social factors due to peer smoking 100%, psychological to get 88.9% comfort, biological factors to experiment 94.4%, parental parenting 72.2% and 100% the impact of smoking are Asthma 1 person (5.6%), Cold 18 people (100%), and cough 18 people (94.5%%). Factors that most influence adolescent smoking are biological factors 94,4%, followed by the psychological influence of 88,9%, then parenting factors 72,2%, Most cigarette smoking effect is cough (100%). It is recommended that both parents, community leaders, religious leaders and the government conduct various activities so that adolescents do not smoke as well as periodical education about the dangers of smoking for teenagers by health workers.